2013
DOI: 10.1074/jbc.m113.465575
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (IL)-32β-mediated CCAAT/Enhancer-binding Protein α (C/EBPα) Phosphorylation by Protein Kinase Cδ (PKCδ) Abrogates the Inhibitory Effect of C/EBPα on IL-10 Production

Abstract: Background: IL-32␤ promotes IL-10 production in myeloid cells. Results: IL-32␤-mediated C/EBP␣ serine 21 phosphorylation by PKC␦ induced the dissociation of C/EBP␣ from IL-10 promoter, thereby promoting IL-10 production. Conclusion: IL-32␤ suppressed the inhibitory effect of C/EBP␣ on IL-10 production by mediating C/EBP␣ serine 21 phosphorylation by PKC␦. Significance: Our data suggest that IL-32␤ functions as an intracellular regulator of IL-10 production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 34 publications
1
44
0
Order By: Relevance
“…Three isoforms of IL-32 (η, θ, s) were recently identified by our group [12]. The IL-32α and IL-32β isoforms are the most abundant in A549 lung cancer cells and U937 myeloid lymphoma cells, respectively, whereas IL-32ε and IL-32ζ are both expressed in T cells [9,13,14]. IL-32 has bifunctional effects on the immune response in that it can induce the expression of not only pro-inflammatory cytokines, including tumor necrosis factor α (TNF-α) and IL-1β [6], but also the anti-inflammatory cytokine, IL-10 [15].…”
Section: Introductionmentioning
confidence: 98%
“…Three isoforms of IL-32 (η, θ, s) were recently identified by our group [12]. The IL-32α and IL-32β isoforms are the most abundant in A549 lung cancer cells and U937 myeloid lymphoma cells, respectively, whereas IL-32ε and IL-32ζ are both expressed in T cells [9,13,14]. IL-32 has bifunctional effects on the immune response in that it can induce the expression of not only pro-inflammatory cytokines, including tumor necrosis factor α (TNF-α) and IL-1β [6], but also the anti-inflammatory cytokine, IL-10 [15].…”
Section: Introductionmentioning
confidence: 98%
“…Rottlerin has generally been used as a specific inhibitor for PKCδ (Gschwendt et al, 1994;Kang et al, 2013). However, our previous Control, n=46 cells (four slices); Jnk1-sh788, n=49 cells (five slices); Jnk1-sh788+wt-Jnk1, n=58 cells (five slices).…”
Section: Jnk Regulates Nuclear Elongation But Not Dilation Formationmentioning
confidence: 99%
“…Recently, Kang et al demonstrated that IL-32 interacts with PKCε and STAT3 to induce IL-6 expression in monocytic THP-1 cells (28). The interaction of PKC␦, IL-32, and C/EBP␣ suppressed the inhibitory effects of C/EBP␣ on the IL-10 promoter in myeloid cells (47). These studies suggested that IL-32 may modulate various functions by interacting with different proteins in different cell types.…”
Section: Discussionmentioning
confidence: 97%
“…5B show that knockdown of IL-32 did not induce PARP or caspase-3 cleavage, suggesting that depletion of IL-32 does not affect apoptosis. Previous studies demonstrated that IL-32 enhances IL-6, IL-8, and IL-10 (29,46,47). In addition, these cytokines have been induced by LMP1 (48)(49)(50).…”
Section: Expression Pattern and Cellular Distribution Of Il-32 Inmentioning
confidence: 99%